2011
DOI: 10.1111/j.1747-7379.2011.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Cross-Ethnic Friends by Recent Immigrants in Canada: A Longitudinal Approach

Abstract: This paper examines the development of inter-ethnic friendships between immigrants and Canadians. It uses longitudinal data from three waves of the Canadian LSIC survey, in which newly arrived immigrants were followed during the first 4 years of settlement. It is found that pre-migration characteristics play an important role in the development of inter-ethnic friendships: immigrants who arrive at a younger age and for economic reasons, as well as those who are highly educated and have a cross-ethnic partner a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
3
26
0
1
Order By: Relevance
“…Since adolescents often meet new people through their friends (Grossetti, 2005), if they have friends from different ethnic backgrounds they are more likely to form additional interethnic friendships (Ellison and Powers, 1994;Martinovic et al, 2011). Thus, ethnic friendship segregation may reinforce itself over time.…”
Section: Introductionmentioning
confidence: 95%
“…Since adolescents often meet new people through their friends (Grossetti, 2005), if they have friends from different ethnic backgrounds they are more likely to form additional interethnic friendships (Ellison and Powers, 1994;Martinovic et al, 2011). Thus, ethnic friendship segregation may reinforce itself over time.…”
Section: Introductionmentioning
confidence: 95%
“…Longitudinally, Stoessel, Titzmann, and Silbereisen (2012) found that stronger identification with the mainstream cultural group predicted greater social participation over time in that group, among adolescent diaspora immigrants to Germany and Israel. Finally, even outside of psychology, longitudinal research in demography using a large scale national survey showed that immigrants to Canada who rated the importance of Canadian traditions higher in the first year post-migration reported more numerous inter-ethnic friendships during the following three years (Martinovic, van Tubergen, & Maas, 2011).…”
Section: Cultural Orientations As Predictors Of Social Participationmentioning
confidence: 99%
“…Following this notion, it was hypothesised that a preference for culture maintenance would increase intragroup friendships, that is, would make it more likely that friendships with other minority group members would be sought. A preference for culture adoption, in contrast, would lead to increased intergroup friendships with majority members (Martinovic et al, ). After all, strong intragroup ties might be one means through which culture maintenance can be achieved, which implies that a positive effect of culture maintenance desire on intragroup friendships should be expected.…”
Section: Identification and Acculturation Preferencesmentioning
confidence: 99%
“…Although some antecedents are known (e.g. Binder et al, ; Martinovic, van Tubergen, & Maas, ; West, Pearson, Dovidio, Shelton, & Trail, ), overall the antecedents of intergroup friendships are much less well understood than its consequences. The present research addresses this question.…”
mentioning
confidence: 99%